The impact of strategic alignment on organizational performance: The case of Ethiopian universities - Dawit Udessa Gede; Admasu Tesso Huluka (Cogent Business & Management, 2023)
Strategic alignment deals with organizational strategic fit with functional areas strategies, such as human resources management strategy. It is based on goal setting premise which believes in collaborative effort that involves all parties imagining and working towards a common aim in tandem. Strategic alignment in this study takes assumption of goal setting theory stressed on importance of clarity of the goal to perform at the highest level and achieve success. The purpose of this study was to look into the impact of strategic alignment on organizational performance. Clarity in the aim, role clarity, and process clarity were discovered and examined for the measurement of organizational strategic alignment. The study took a quantitative approach with descriptive and explanatory research designs. Three Ethiopian universities were chosen based on generation of establishment to include 365 personnel in the sample using a random selection technique. Descriptive statistical tools such as mean and standard deviation were used, whereas structural equation models were used for confirmatory factor analysis and path analysis. According to the study's findings, goal clarity, role clarity, and process clarity all have a significant and favorable effect on organizational performance in higher education. Findings of the study reveal also that organizational performance varies among study institution based on implementation level of strategic alignment. Based on the study's findings, it is recommended that organizational leaders outline organizational strategic intents with specific goals. Thus, it is recommended that governing bodies need to promote defined roles and processes for all workers.
Keywords: 650; alignment; clarity; goal; performance; process; role; strategy